Rediscovery of Passiflora danielii Killip, 1960 (subgenus Passiflora): a threatened narrow endemic species of Colombia - Ocampo, John; Restrepo, Jorge Julián; Giraldo, Wilmer (Pensoft Publishers, 2015)
Passiflora danielii, an endemic species to Colombia, which is threatened, was rediscovered in the Department of Antioquia, where it has not been reported since 1938. The species was only known from the type locality (Municipality of Cocorná). Now, four new locations are added near it. The current study further presents a revised morphological description of P. danielii based on fresh material, along with an updated distribution map. Finally, following the IUCN Red List Criteria, P. danielii was classified as Critically Endangered (CR) species.